Key Performance Indicators in Irish Hospital Libraries: Developing Outcome-Based Metrics to Support Advocacy and Service Delivery - Dalton, Michelle (Evidence Based Library and Information Practice, 2012)
Objective – To develop a set of generic outcome-based performance measures for Irish hospital libraries. Methods – Various models and frameworks of performance measurement were used as a theoretical paradigm to link the impact of library services directly with measurable healthcare objectives and outcomes. Strategic objectives were identified, mapped to performance indicators, and finally translated into response choices to a single-question online survey for distribution via email. Results – The set of performance indicators represents an impact assessment tool which is easy to administer across a variety of healthcare settings. In using a model directly aligned with the mission and goals of the organization, and linked to core activities and operations in an accountable way, the indicators can also be used as a channel through which to implement action, change, and improvement. Conclusion – The indicators can be adopted at a local and potentially a national level, as both a tool for advocacy and to assess and improve service delivery at a macro level. To overcome the constraints posed by necessary simplifications, substantial further research is needed by hospital libraries to develop more sophisticated and meaningful measures of impact to further aid decision making at a micro level.